2012
DOI: 10.4103/2277-9531.98572
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Health Belief Model based intervention on promoting nutritional behaviors about osteoporosis prevention among students of female middle schools in Isfahan, Iran

Abstract: Background:Osteoporosis is a systemic skeletal disorder characterized by reduction of one mass, deterioration of bone structure, increasing bone fragility, and increasing fracture risk. Prevention of osteoporosis during childhood and adolescence is one of the most important issues in World Health Organization. The purpose of this study was to determine the effect of Health Belief Model based intervention on promoting nutritional behaviors about preventive osteoporosis among the second grade middle school girl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 9 publications
8
34
0
Order By: Relevance
“…This showed the effect of educational intervention on the increase in perceived susceptibility of women in reproductive age, meaning that most women believed that they might have a risk of osteoporosis after the intervention. The results of this study are consistent with Khorsandi et al, Ebadi Fard Azar et al and Ghaffari et al [21][22][23] .…”
Section: Discussionsupporting
confidence: 93%
“…This showed the effect of educational intervention on the increase in perceived susceptibility of women in reproductive age, meaning that most women believed that they might have a risk of osteoporosis after the intervention. The results of this study are consistent with Khorsandi et al, Ebadi Fard Azar et al and Ghaffari et al [21][22][23] .…”
Section: Discussionsupporting
confidence: 93%
“…Before the intervention, perceived susceptibility scores of the participants was moderate. Piaseu et al, Hazavehei et al and Ghaffari et al [23] suggested that educational intervention increased perceptive susceptibility in young girls. Thus it is prudent to provide the necessary education about osteoporosis to female Iranian adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…According to our findings, education based on HBM can alter staff behavior regarding adherence to SPs, such as washing hands, using personal safety tools (gloves, hat, gown, mask, and glasses), prevention of needlestick injury, and taking necessary measures in the vicinity of sharp and cutting objects. In similar studies, education based on the HBM could affect behaviors regarding the prevention of needlestick injury, adherence to SPs in medical students, controlling hospital infection, and increasing vaccination rates in college men (23)(24)(25)31).…”
Section: Discussionmentioning
confidence: 99%
“…The HBM has been used for teaching SPs and controlling infections (23), such as by preventing needlestick injuries (14), medical students' compliance with SPs (24), and nurses' behavior in preventing hospital infections (25). Although some studies have shown that education based on HBM can alter the adherence to SPs, as the investigators pointed out, it is still important to use this model to investigate the effects of education on the adherence to SPs by OR staff.…”
Section: Introductionmentioning
confidence: 99%